Partitioning Behavior of Papain in Ionic Liquids-Based Aqueous Two-Phase Systems - Zhiwen Bai; Yanhong Chao; Meiling Zhang; Changri Han; Wenshuai Zhu; Yonghui Chang; Huaming Li; Yang Sun (Journal of Chemistry)
This paper attempts to study and optimize the affinity partitioning conditions of papain in an aqueous two-phase system (ATPS). The effect of the amount of ionic liquids (ILs), the concentration of K2HPO4, temperature, pH, and the volume of papain solution were discussed concretely. The optimum conditions were determined as ionic liquid was 1.4 g and K2HPO4 was 1.4 g, the extraction efficiency of papain could reach 98.33% with pH unadjusted. The temperature and the pH of the solution are major parameters that influence the partitioning of protein in ILs-based ATPSs. The partition of papain to the IL-rich phase was enhanced by increasing the amount of ILs, the concentration of K2HPO4, and temperature, especially at its isoelectric point.